Global status of groundfish stocks - Hilborn, Ray (2021)
We review the status of groundfish stocks using published scientific assessments for 349 individual stocks constituting 90% of global groundfish catch. Overall, average stock abundance is increasing and is currently above the level that would produce maximum sustainable yield (MSY). Fishing pressure for cod-like fishes (Gadiformes) and flatfishes (Pleuronectiformes) was, for several decades, on average well above levels associated with MSY, but is now at or below the level expected to produce MSY. In contrast, fishing pressure for rockfishes (Scorpaeniformes) decreased from near MSY-related levels in the mid-1990s, and since the mid-2000s has remained on average at only one third of MSY-related levels. Regions with the most depressed groundfish stocks are the Northwest Atlantic and the Pacific coast of South America, while stocks from the Northeast and Eastern Central Pacific, Northeast Atlantic, Southeast Atlantic and Southwest Pacific tend to have greatest average abundance relative to MSY-based reference points. In the most recent year available for each stock, the catch was only 61% of MSY. Equilibrium yield curves indicate that 76% of global potential groundfish yield could be achieved using current estimates of fishing pressure. 15% of this is lost by excess fishing pressure, 67% results from lower than optimal fishing pressure on healthy stocks and 18% is lost from stocks currently overfished but rebuilding. Thus, there is modest opportunity to increase catch of global groundfish fisheries by reducing overfishing on some stocks, but more by increasing harvest on others. However, there may be other reasons not to fully exploit these stocks.